2019
DOI: 10.7899/jce-18-13
|View full text |Cite
|
Sign up to set email alerts
|

Student and new graduate perception of hospital versus institutional clinic for clinical educational experience

Abstract: Objective: To explore final-year students and new graduates from 2 North American chiropractic colleges regarding perceptions of the clinical educational experience in a hospital vs the institutional clinical setting. Methods: A qualitative exploratory descriptive design was used for this research. Students and new graduates were invited to participate from a United States and Canadian chiropractic college. Semistructured interviews were conducted with 49 students and 14 new graduates lasting 60 minutes. Conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…The importance of chiropractic student exposure to a broad patient case mix during student residencies has been previously discussed. 14,32 While accreditation standards for Australian chiropractic training programs do not mandate specific requirements around patient case mix, 8 it is expected that by graduation students will be exposed to a sufficiently broad patient case load during their clinical internship to provide safe and effective patient care across different patient populations. Uncertainty therefore remains as to whether chiropractic graduate students are sufficiently exposed to a broad range of headache types during their clinical internship training in order to be adequately prepared for effective headache patient management.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of chiropractic student exposure to a broad patient case mix during student residencies has been previously discussed. 14,32 While accreditation standards for Australian chiropractic training programs do not mandate specific requirements around patient case mix, 8 it is expected that by graduation students will be exposed to a sufficiently broad patient case load during their clinical internship to provide safe and effective patient care across different patient populations. Uncertainty therefore remains as to whether chiropractic graduate students are sufficiently exposed to a broad range of headache types during their clinical internship training in order to be adequately prepared for effective headache patient management.…”
Section: Discussionmentioning
confidence: 99%
“…8 Previous international studies have identified that chiropractic graduate students can perceive themselves to be unprepared within certain clinical competencies, raising concerns about gaps that may exist between student education and practice-ready practitioners. [13][14][15] To date, little research has specifically examined chiropractic students' perceived preparedness and ability to diagnose and manage headache disorders. In direct response to this research gap, the primary aim of this study was to assess 4th-and 5th-year Australian chiropractic students' selfperceived preparedness for headache disorder diagnosis and management, as well as their performance (correctness) in headache diagnosis and management decision making.…”
Section: Introductionmentioning
confidence: 99%
“…This has been commonly found in other studies as disadvantages of the institution-based clinics and advantages of community-based clinics and hospital placements. 16 Students and academics alike desire students to be exposed to diverse patient populations, often with comorbidities, to assist in developing students' clinical and professional skills, competence, capability, and confidence: the feeling of being more clinically prepared. Academics and students alike know that the foundation of skills attained through a scaffolded program with placement in the UHC can also contribute to this preparedness.…”
Section: Professional Identitymentioning
confidence: 99%
“…Providing a wide range of experiences will ensure students' ability to meet graduate expectations; thus, graduates will be fit for the purpose: well prepared primary care chiropractic or osteopathic physicians. 1,16,37,38…”
Section: Professional Identitymentioning
confidence: 99%
See 1 more Smart Citation